2014
DOI: 10.1002/rra.2848
|View full text |Cite
|
Sign up to set email alerts
|

Hydromorphology Meets Mammal Ecology: River Morphological Quality, Recent Channel Adjustments and Otter Resilience

Abstract: The need for a multidisciplinary approach for characterizing water bodies in terms of morphological, chemical and ecological quality has hastened the growth of hydromorphology as a cross-disciplinary topic at the interface of hydrology, geomorphology and ecology. Many authors have analysed how hydroecology may affect freshwater biodiversity, although little is known about how this biodiversity might be affected by river morphological quality. We examined how well the presence of the semi-aquatic Eurasian otter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…In this study, the selected target species were the Eurasian otter (Lutra lutra) and water deer (Hydropotes inermis). The otter is a flagship threatened species, and is also one of the key species in riparian ecosystems (Stevens, Organ, and Serfass 2011;Scorpio et al 2014); their range covers most of Europe and Asia and can be a useful indicator for the evaluation of ecological disturbances or for conservation planning (SoulĂ© and Terborgh 1999). White, McClean, and Woodroffe (2003) showed that habitat types associated with spraints and not the density and height of vegetation affect the otter's habitat characteristics.…”
Section: Target Wildlife Species and Habitat Component Selectionmentioning
confidence: 99%
“…In this study, the selected target species were the Eurasian otter (Lutra lutra) and water deer (Hydropotes inermis). The otter is a flagship threatened species, and is also one of the key species in riparian ecosystems (Stevens, Organ, and Serfass 2011;Scorpio et al 2014); their range covers most of Europe and Asia and can be a useful indicator for the evaluation of ecological disturbances or for conservation planning (SoulĂ© and Terborgh 1999). White, McClean, and Woodroffe (2003) showed that habitat types associated with spraints and not the density and height of vegetation affect the otter's habitat characteristics.…”
Section: Target Wildlife Species and Habitat Component Selectionmentioning
confidence: 99%
“…At present, the Southern-Italian population, geographically and genetically isolated from all otter populations living in Europe (Spagnesi, 2002;Randi et al, 2003), occurs in a continuous range from Abruzzo to Basilicata, Calabria and Apulia (Giovacchini et al, 2018). Despite a general positive trend and a slow recovery with an expansion northward (Fusillo, Marcelli & Boitani, 2003;De Castro & Loy, 2007;Prigioni, Balestrieri & Remonti, 2007;Balestrieri et al, 2008;Loy et al, 2009;Buglione et al, in press), the otter in Italy is one of the most threatened mammals, listed as Endangered (EN, category D) on the Official Italian Red List (Loy et al, 2010;Rondinini et al, 2013;Scorpio et al, 2014), both at national and local levels.…”
Section: Introductionmentioning
confidence: 99%
“…The Eurasian otter (Lutra lutra, Linnaeus 1758) has suffered a marked decline in many European countries during the second half of the twentieth century, due to the combination of global and local factors, such as human persecution, pollution, and habitat fragmentation (Mason, 1995;Murk et al, 1998;Conroy & Chanin, 2000;Mason & Wren, 2001;Ruiz-Olmo et al, 2002;Panzacchi et al, 2011;Scorpio et al, 2016).…”
Section: Introductionmentioning
confidence: 99%